Analisis Break Event Point (BEP) Dalam Penetapan Tarif Jasa Pengacara Pada Kantor Hukum Riko Santoso, S.H & Patner - Meylita Putri Dibyanto; Fefti Yulian Mela; Zulkarnain (AKPEM : Jurnal Akuntansi Keuangan dan Pemerintahan, 2026)
The purpose of this study was to determine the break-even point achieved by the Riko Santoso, SH & Partners Law Firm in carrying out its business activities, to determine how to calculate the costs of each incoming case based on the type of case, and finally, to determine the results of the Break-Even Point Analysis that can be used as a basis for determining efficient and sustainable legal service fees. The results of this study are the BEP calculations in several cases calculated by the Riko Santoso, SH & Partners Law Firm, which obtained varying results in each case. In the divorce case, the BEP Unit calculation was obtained as many as 4 cases, a BEP Rupiah of Rp. 5,466,450, and a MOS of 89%. In the Isbat Nikah case, the BEP Unit calculation was obtained as many as 5 cases, a BEP Rupiah of Rp. 6,393,671, and a MOS of 29%. In the Marriage Dispensation case, the BEP Unit calculation was obtained as many as 5 cases, a BEP Rupiah of Rp. 7,427,941 and MOS -24%, thus indicating that the BEP calculation is safe in Divorce and Marriage Confirmation cases, while the BEP calculation is not safe or negative in Marriage Dispensation cases.